2016
DOI: 10.1108/ijse-08-2015-0199
|View full text |Cite
|
Sign up to set email alerts
|

The effect of health expenditure on selected maternal and child health outcomes in Sub-Saharan Africa

Abstract: Purpose The purpose of this paper is to investigate the effect of public and private health expenditures on selected maternal-child health outcomes in Sub-Saharan Africa (SSA). Design/methodology/approach The study utilizes panel data on 40 SSA countries spanning the period 2000-2010. The data are analyzed using the fixed effects estimation technique. Findings The results indicate that public health expenditure is inversely and significantly related to infant (IMRR) and under-five (U5MR) mortalities in SSA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
30
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 26 publications
8
30
2
Order By: Relevance
“…Nicholas et al () discovered the same for 40 SSA countries. Akinlo and Sulola () examined the effects of PHE on infant mortality in 10 SSA countries from 2000 to 2008.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 78%
See 1 more Smart Citation
“…Nicholas et al () discovered the same for 40 SSA countries. Akinlo and Sulola () examined the effects of PHE on infant mortality in 10 SSA countries from 2000 to 2008.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 78%
“…The literature is by no means shut of studies on the nexus between the environment, PHE, and health status. Recent studies that have examined this link include (Akinlo & Sulola, ; Becchetti, Conzo, & Salustri, ; Dhrifi, , ; Gomis‐Porqueras, Moslehi, & Suen, ; Jaba, Balan, & Robu, ; Kato, Mugarura, Kaberuka, Matovu, & Yawe, ; Li, Fujiura, Magaña, & Parish, ; Liang & Tussing, ; Linden & Ray, ; Nicholas, Edward, & Bernardin, ; Rahman, Khanam, & Rahman, ; van den Heuvel & Olaroiu, ; Ventelou & Abu‐Zaineh, ). Edeme et al () investigated the effect of PHE and urbanization on two different health status indicators in Nigeria from 1981 to 2014.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…Similarly, Self and Grabowski [ 17 ] found that HE has a significant impact on health only in low and middle-income countries. Furthermore, Bidani and Ravallion [ 18 ] and Nicholas et al [ 19 ] stated that public HE is useful for the poor but not for the non-poor (high-income) in improving HO. Nicholas et al [ 19 ] also concluded that private HE has no significant impact in reducing child and maternal mortality in 40 countries of sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Bidani and Ravallion [ 18 ] and Nicholas et al [ 19 ] stated that public HE is useful for the poor but not for the non-poor (high-income) in improving HO. Nicholas et al [ 19 ] also concluded that private HE has no significant impact in reducing child and maternal mortality in 40 countries of sub-Saharan Africa. Similar results were also found by Anyanwu and Erhijakpor [ 20 ] for 47 African countries and Farag et al [ 12 ] for 133 low and middle income countries.…”
Section: Introductionmentioning
confidence: 99%
“…By the time a health worker is assigned responsibility to render health services, they are competent and therefore unlikely to make mistakes while on duty. This contradicts with Ashiabi et al (25), who ascertained that due to the busy schedule and burnout of health workers, they sometimes provide wrong prescriptions and are responsible for a reasonable number of miscarriages encountered by adolescents. In this regard, a lack of consistency suggests that further research should be conducted about the same subject.…”
Section: Challenges Accessing Maternal Health Servicesmentioning
confidence: 77%